Transmission Power Adaption Technique for VANET by Using Piggyback Information - Nurul Shafiqa, Ahmad Zabidi; Sadiq, Ali Safa (2015)
Vehicular networking has gained a lot of popularity among the industry and shows the great promise but still there are some issues and challenges that need to be considered. An extremely dynamic vehicular can cause a frequent disconnection in the running network applications. This connection occurs depends on high movement of vehicle at high speed make the topology became dynamic. The piggyback information is the target range and feedback beacon. The load on the wireless channel can be reduce if periodic beacon message are transmitted over multiple hops with reduced transmit power instead of being transmitted over one hops with high transmit power. In particular, the possible bandwidth savings that can be achieved by piggyback forwarded message into the own next beacon transmission. The Beacon Power Control (BPC) protocol first sensed and examine the percentage of the channel congestion, the result obtained is use to adjust the transmission power for the safety message to reach the optimal power. This will lead to decrease the congestion in the channel and achieve good channel performance and dissemination.